ITU PENGARUH DIALEK TERHADAP PELAFALAN SISWA DALAM KEMAMPUAN BERBICARA - Syahreni Siregar (Jurnal Pedagogy, 2017)
Dialect is one of the important aspects in language and communication. So that it will also influence the language teaching process. This article aims to discuss deeply about how dialect can influence on the student’s pronuncition in speaking ability. The diversity of Indonesian people influence students’ ability in understanding the subject which learned. One of the diversity is language variation in their daily life which called dialect. Every dialect will have uniqueness when speaking. It influences their ability when speak English. Pronunciation is one of the most important parts of English to communicate with the other people since there are differences between symbols and sounds. To communicate with other people in foreign labguage we should have a good pronunciation so that the listener can understand what we mean and there is no missunderstandig between the speaker and the listener. So, this article will try to find out the influence of dialect on the student’s pronunciation in speaking ability.